OC-002 Predicting Outcome In Acute Ulcerative Colitis: Comparison Of The Travis And Ho Scores Using Uk Ibd Audit Data. (9th June 2014) - Churchhouse, AM; Lynch, RW; Protheroe, A; Arnott, ID
Abstract : Introduction: Patients with severe Ulcerative Colitis (UC) are commonly identified using the Truelove and Witts 1 criteria on presentation. The Travis 2 and Ho 3 scores are subsequently used to identify patients with severe UC who are at high risk of failing medical therapy and needing second line therapy or colectomy. To date there has been no direct comparison between Travis and Ho scores to determine which is superior. Methods: We analysed data from 3049 patients with UC collected during the 2010 round of the UK IBD audit. 984 patients had acute severe UC according to the Truelove and Witts criteria. Those that failed steroid therapy were scored using both Travis and Ho criteria and allocated into either a Travis "high" or "low" risk group and either a Ho "high", "medium" or "low" risk group. We assessed whether further medical or surgical intervention varied between groups. Results: Patients requiring surgery did not differ between the high risk groups (Travis 49%, n = 93 and Ho 51%, n = 84, respectively). However, only 35% (n = 53) in the medium risk Ho group, 26% (n = 17) in the low risk Ho group and 32% (n = 65) in the low risk Travis group underwent surgery. Similarly 41% (n = 78) and 38% (n = 63) of patients in the high risk Travis and Ho groups respectively were treated with ciclosporin, whereas only 34% (n = 51) were treated in the medium risk Ho group, 25% (n = 16) in the low risk Ho group and 27% (n = 55) in the low risk Travis group. Resistance to ciclosporin correlated with increasing risk stratification, although this failed to reach statistical significance for all groups. The use of anti-TNFs was the same across all three groups, although like ciclosporin, the tendency to TNF resistance also increased with increasing risk group. Conclusion: The Travis and Ho scores are equally able to identify patients who are at high risk of failing medical therapy and needing colectomy or second line medical therapy. The Ho score may also be able to identify an intermediate risk group which also has an intermediate response to second line therapy. Both scores are useful tools to aid clinical decision making but do not replace timely multidisciplinary care for these patients. References: 1 Truelove SC, Witts DJ. Cortisone in ulcerative colitis. Br Med J 1955;2(4947):1041–1048 2 Travis SPL, Farrant JM, Ricketts C, Nolan DJ, Mortensen NM, Kettlewell MGW, Jewell DP. Predicting outcome in severe ulcerative colitis. Gut 1996;38(6):905–910 3 Ho GT, Mowat C, Goddard CJR, Fennell JM, Shah NB, Prescott RJ, Satsangi J. Predicting the outcome of severe ulcerative colitis: development of a novel risk score to aid early selection of patients for second-line medical therapy or surgery. Aliment Pharmacol Ther 2004;19(10):1079–87 Disclosure of Interest: None Declared.